The Effectiveness of The Cooperative Integrated Reading and Composition (CIRC) and Preview Question Read Reflect Recite Review (PQ4R) on Reading Comphrehension Skill - Asih Wahyuningsih; Nor Mivtha Citraningrum (Universitas Muhammadiyah Surakarta, 2019)
This research aims to describe the effectiveness of the CIRC and PQ4R models on the reading comprehension skills of the fifth semester students of the PGSD study program. This study uses quasi-experimental design with pretest-posttest nonequivalent group design. This study used two experimental groups and one control group. The population of this study was the fifth semester students of PGSD Study Program. Sampling is done using a simple random sampling technique. To determine the effectiveness of learning CIRC and PQ4R, the data were analyzed using t-test and anava. The results of this study indicate that CIRC learning is effective in learning reading skills understanding of the fifth semester of PGSD Study Program with a significant level of 0.006 <0.05. PQ4R learning is effective in learning reading comprehension skills in students in the fifth grade of elementary school with a significant level showing 0,000 <0,05. The difference in CIRC and PQ4R learning is effective in reading skills. The fifth semester students of PGSD study program with a significance level of 0,000 <0,05.